The anti‐inflammatory peptide Catestatin blocks chemotaxis. Issue 2 (22nd December 2021) - Muntjewerff, Elke M.; Parv, Kristel; Mahata, Sushil K.; van Riessen, N. Koen; Phillipson, Mia; Christoffersson, Gustaf; van den Bogaart, Geert
Abstract: Increased levels of the anti‐inflammatory peptide Catestatin (CST), a cleavage product of the pro‐hormone chromogranin A, correlate with less severe outcomes in hypertension, colitis, and diabetes. However, it is unknown how CST reduces the infiltration of monocytes and macrophages (Mϕs) in inflamed tissues. Here, it is reported that CST blocks leukocyte migration toward inflammatory chemokines. By in vitro and in vivo migration assays, it is shown that although CST itself is chemotactic, it blocks migration of monocytes and neutrophils to inflammatory attracting factor CC‐chemokine ligand 2 (CCL2) and C‐X‐C motif chemokine ligand 2 (CXCL2). Moreover, it directs CX3 CR1 + Mϕs away from pancreatic islets. These findings suggest that the anti‐inflammatory actions of CST are partly caused by its regulation of chemotaxis. Graphical Abstract: Catestatin blocks monocyte and granulocyte migration toward inflammatory chemokines.